Helicobacter pylori co infection in patients with typhoid fever - Seyyed Mohammad Alavi (MD); Arash Etemad (MD); Mehrdad Azmi (MD) (مجله دانشگاه علوم پزشکی گرگان, 2009)
Background and Objective: There are some reports on the association between helicobacter pylori infection and typhoid fever in different parts of the world. The aim of this study was to estimate the co infection of helicobacter pylori and typhoid fever in Ahwaz city in South-West of Iran.